Effects of various hyperopia intervention levels on male college students’ gait kinematics - Zeng, Zhaohong; Xue, Aochuan; Wang, Huihui; Zha, Xianjun; Ji, Zhongqiu (Frontiers in Physiology, 2023)
BACKGROUND: Hyperopia is a common blurred vision phenomenon that affects postural control in gait; however, current research has focused on the alteration and correction of hyperopia's physiological characteristics, ignoring the effect of hyperopia on gait kinematic characteristics. The effect of hyperopia on the basic form of movement walking is a worthy concern. OBJECTIVE: To investigate the gait kinematic characteristics of male college students with varying degrees of visual acuity (normal vision, hyperopia 150°, and hyperopia 450°), as well as to provide a theoretical foundation for the effect of visual acuity on gait and fall risk reduction. METHODS: Twenty-two male college students with normal visual acuity were chosen, and their vision was tested using a standard visual acuity logarithm table at normal and with 150° and 450° concave lenses, and gait kinematic data were collected under hyperopic conditions using the PN3 Pro advanced inertial motion capture system and Axis Studio application program. Results and conclusions: 1. the change in center of gravity in Pre-double support was smaller than normal vision; the change in center of gravity in Late-single support and Late-swing was larger than normal vision; 2. the percentage of Late-double support was smaller than normal vision; 3. Hip inversion and abduction, internal rotation, and external rotation are larger than normal vision in Late-single support; knee and ankle flexion and extension, inversion and abduction, internal rotation, and external rotation are larger than normal vision in the swing stage; hip flexion and extension, internal rotation, and external rotation are larger than normal vision in the swing stage. Hyperopic interventions have an impact on the kinematic characteristics of gait in male college students, mainly in terms of altered balance, increased instability, increased difficulty in maintaining trunk stability, and increased risk of injury.